Methodology to evaluate the balance in multicomponent economic systems of regions - Юрий Мальцев (Вестник Пермского университета: Серия Экономика)
Introduction. The balanced development of regional systems is an important prerequisite for their sustainable performance. Regional economic systems consist of many interacting components. Modern scientific literature gives no methods designed to evaluate the balance of multicomponent regional systems. The purpose of the study is to develop a methodology for assessing the balance of multicomponent economic systems of regions and test it with the data of the regions of the Russian Federation, when the regions are considered to be two-, three- and four-component systems. Tasks are as follows: to plot a balance evaluation function, to develop a balance evaluation algorithm for the multicomponent economic systems in the regions, and to assess the balance of economic systems for the regions of the Russian Federation. Materials and Methods. The balance evaluation methodology is determined by the fact that a region is seen to be a system with many interacting components or N-components. This generalization facilitates a wide range of tools for assessing the balance of economic activities with the data of the regions. To test the methodology, we use the data from All-Russian Classifier of Economic Activities. Reference to a multicomponent system groups a large number of parameters with no significant calculation complexity, which provides great opportunities to use the method with no reference to large volumes of data and a number of parameters. Results. The developed method was tested with the data concerning the regions of the Russian Federation; the results were compared. This approach evaluates the proportions of the regions with a large number of input parameters with no significant calculating complexity. Most regions are shown to have either a low or medium level of balance. The results also clearly illustrate the impact of an environmental component on the balance of the region. Conclusions. The proposed approach to modeling the balance in regions’ economic activities can be useful for making efficient management decisions and developing growth strategies for regional systems.